Mullite cytotoxicity and cell adhesion studies - Fernandes, Leandro (2019)
Mullite is a low cost ceramic material based on aluminous silicate and synthesized via solid state reaction. Mullite displays potential properties for application in the biomedical field, specially its high mechanical strength, however it is poorly characterized with respect to its specific cytotoxicity and capability to allow the cell adhesion to its surface. Here, mullite was prepared by sintering the mixture of Al2O3 and SiO2 at 1500 °C and characterized. Its elastic modulus was 135 GPa and its flexural strength, 109 MPa. The study of the viability of GM07492 human cells in presence of mullite revealed the proliferation and adhesion of the cells on its surface, which is an indication of biocompatibility. Its good mechanical properties and cytocompatibility suggested that mullite can be used as an alternative material for biomedical applications and dentistry.